CORRELATION BETWEEN COMPUTED-TOMOGRAPHY AND MAGNETIC-RESONANCE-IMAGING IN DIASTEMATOMYELIA - (:unkn) unknown (ELSEVIER SCI IRELAND LTD, 1991)
Preoperative neuroradiological evaluation of diastematomyelia cases is of vital importance in order to increase surgical success rate. This paper reports the neuroradiological data of diastematomyelia cases in the light of surgical findings, and discusses the efficacy of CT and MRI in the evaluation of patients with diastematomyelia.
Keywords: DIASTEMATOMYELIA; CT; MAGNETIC RESONANCE IMAGING; CNS; COMPUTED TOMOGRAPHY; CNS